PENGOPTIMALAN BIAYA TRANSPORTASI DENGAN METODE LEAST COST DAN LINGO UNTUK DISTRIBUSI SABUN BATANG DI PT XYZ - Rhema Chintya Lestari; Mas Muhammad Rizki Aditya; Muchammad Fauzi (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2021)
Transportation models play an important role in controlling shipping costs and distributing products in a company. Each company has a different way of distributing products. Uneven distribution to the company, making one of the factors of the problem in the progress of the company itself. PT XYZ is one of the bar soap manufacturing companies in Indonesia. The least cost method itself is one of the methods that can be used to optimize transportation and distribution costs. The least cost method prioritizes allocating from the lowest cost in the transportation matrix. LINGO is a simple software that can be used to calculate linear and non-linear optimization values.